Factors Associated With Individual Emergency Preparedness Behaviors: A Cross-Sectional Survey Among the Public in Three Chinese Provinces - Ning, Ning; Hu, Man; Qiao, Jin; Liu, Chaojie; Zhao, Xiaowen; Xu, Wei; Xu, Weilan; Zheng, Bin; Chen, Zhiqiang; Yu, Yi; Hao, Yanhua; Wu, Qunhong (Frontiers in Public Health, 2021)
Introduction: This study aimed to identify factors associated with individual emergency preparedness behaviors which play an important role in effective emergency response. Methods: Data were drawn from a cross-sectional survey conducted in China's Heilongjiang, Guangdong and Sichuan provinces in 2017. Questionnaires were administered through face-to-face interviews, and 2,506 were valid for data analyses. A structural equation model was established to test the direct and indirect effects of the relevant factors on individual emergency preparedness behaviors. Results: Low levels of emergency preparedness were found: 28% of respondents reported being fully/partly prepared. The attitudes of the respondents toward emergency preparedness had the strongest association with emergency preparedness behaviors, with a total effect of 0.483. This was followed by self-efficacy (0.305) and training/exercise (0.295). Risk perception had the weakest effect (0.045) on emergency preparedness behaviors. Discussion: Improving attitudes of the public as well as their ability to prepare for emergency events is important for effective emergency management.